2011
DOI: 10.1039/c0em00596g
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged toxicity characteristic leaching procedure for nickel and copper aluminates

Abstract: The toxicity characteristic leaching procedure (TCLP) is a regulatory testing method widely employed to evaluate the environmental friendliness of waste materials. TCLP analysis provides a fast, easy and economical way to determine the mobility of waste pollutants under simulated landfill conditions. Recent studies on metal stabilization have reported the potential for nickel and copper aluminates to form in thermal treatment conditions, and suggested a more reliable method of stabilizing hazardous metals, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The leachability of single-phase ZnO and ZnAl 2 O 4 samples was performed by a modification of the U.S. EPA Toxicity Characteristic Leaching Procedure (TCLP) (TCLP) [25], with a pH 2.9 acetic acid solution (extraction fluid #2) as the leaching fluid. Each leaching vial was filled with 40 mL of TCLP extraction fluid and 2.0 g of ground powder.…”
Section: Characterization and Testmentioning
confidence: 99%
“…The leachability of single-phase ZnO and ZnAl 2 O 4 samples was performed by a modification of the U.S. EPA Toxicity Characteristic Leaching Procedure (TCLP) (TCLP) [25], with a pH 2.9 acetic acid solution (extraction fluid #2) as the leaching fluid. Each leaching vial was filled with 40 mL of TCLP extraction fluid and 2.0 g of ground powder.…”
Section: Characterization and Testmentioning
confidence: 99%
“…When a-Al 2 O 3 was used as the sintering precursor, the leaching of aluminum was extremely low at temperatures <850°C. Although low aluminum leachability has been reported for CuAl 2 O 4 (Tang et al, 2010;Shih and Tang, 2011), because the aluminum concentration in the leachate gradually increased with an increase in sintering temperature, CuAl 2 O 4 is likely still slightly more vulnerable to acidic attack compared to a-Al 2 O 3 . At temperatures >1100°C, the leachability of aluminum further increased and the formation of the CuAlO 2 phase at higher temperatures made the aluminum even more leachable from the solid.…”
Section: Leaching Performance Of Sintered Samplesmentioning
confidence: 91%
“…The increase in copper in the leachate is likely due to the reappearance of CuO and the generation of the CuAlO 2 phase in the sample. Shih and Tang (2011) reported the weaker resistance of CuAlO 2 than CuAl 2 O 4 under acidic attack and this may explain why the copper concentration in the leachate rose again for samples sintered at P1150°C.…”
Section: Leaching Performance Of Sintered Samplesmentioning
confidence: 91%
“…Previous studies have reported that nickel and copper sludge can be incorporated into aluminate and ferrite structures in ceramics through a wellcontrolled sintering process, significantly reducing product leachability through the intrinsic properties of the product phases. [13][14][15][16][17] Ceramics encompass a wide variety of construction and industrial products (e.g. tiles, bricks, and insulation and refractory products).…”
Section: Introductionmentioning
confidence: 99%